When identity meets strategy: The development of British and German anti-torture policies since 9/11 - Heaphy, Janina (Cooperation and Conflict, 2023)
Since 9/11, considerable research has been done on US interrogation and detention operations, but comparatively little is known about the involvement of other traditionally liberal states’ intelligence agencies and their evolving perspectives on torture-related policies for foreigners abroad. Particularly, the United Kingdom and Germany provide interesting cases; despite similar levels of public and political pressure regarding their indirect involvement in Central Intelligence Agency’s operations, the two states took different strategic decisions in 2010 on whether to implement new extraterritorial human rights safeguards. While the United Kingdom introduced a new intelligence guidance for interrogations overseas, the German government opted for policy-continuance, which raises the question why the two states embarked on different policy trajectories, even if they found themselves in contextually similar situations and were subjected to the comparable accountability measures. By bridging insights from Rationalist and normative literature, the article addresses this conundrum by clearly outlining the states’ differing strategic preferences, and by dissecting the multi-layered composition of these interests. As a result, the article delineates how strategic constraints pertaining to the states’ national, international, or political elite level affect decision-makers’ policy responses.
Created from Fastlane, Scopus look-up
Keywords: convention against torture; counterterrorism; foreign policy; Germany; human rights; identity; rational-choice; UK